Cerebrovascular Reactivity After Sport Concussion: From Acute Injury to 1 Year After Medical Clearance - Churchill, Nathan W.; Hutchison, Michael G.; Graham, Simon J.; Schweizer, Tom A. (Frontiers in Neurology, 2020)
Neuroimaging has identified significant disturbances in cerebrovascular reactivity (CVR) in the early symptomatic phase of sport-related concussion. However, less is known about how whole-brain alterations in CVR evolve after concussion and whether they remain present beyond medical clearance to return to play (RTP). In the present study, CVR was evaluated using blood-oxygenation-level-dependent functional magnetic resonance imaging (BOLD fMRI) during a respiratory challenge. Imaging data were collected for 110 university-level athletes, including 39 concussed athletes and 71 athletic controls. The concussed athletes were imaged at the acute phase of injury (1–7 days post-injury), the subacute phase (8-14 days post-injury), medical clearance to RTP, 1 month post-RTP, and 1 year post-RTP. Enhanced negative BOLD response to controlled breathing was seen at acute injury, with attenuation of the effect mainly occurring by 1 year post-RTP. Secondary analyses showed that greater symptom severity and prolonged recovery were associated with enhanced BOLD response in the acute phase of injury, but a more attenuated BOLD response in the subacute phase. This study provides novel information characterizing the CVR response after concussion and shows CVR to be a sensitive technique for evaluating long-term brain recovery.